Waste Utilization and Creative Economy: Efforts to Build Environmentally Concerned Characters for Students at SDN Nglumber II Kepohbaru Bojonegoro - Rohmatul Faizah; Aldira Mara Ditta Caesar Purwanto (VSJ | Veteran Society : Jurnal Pengabdian Masyarakat, 2022)
Increasing the involvement of students in utilizing plastic waste in elementary schools (SD) is a very important thing to do. This paper aims to determine the involvement of students in collecting, sorting, processing, and utilizing waste to support the creative economy program. Instilling awareness of environmental values ​​in all school members is something that must be applied from an early age. There is an effort to encourage students to use both organic and inorganic waste for recycling so that it is more useful. This process cannot be carried out without the role of educators or prospective educators who direct, motivate and practice directly how to process and utilize waste. This study uses a qualitative research approach with interviews, observations, and documentation and uses triangulation techniques to obtain the validity of the data whose purpose is to understand and at the same time explore a real event at the research site. From the results of research on increasing student involvement in utilizing waste, especially plastic waste to support the creative economy, it is highly accepted by all circles in the school environment, especially by students to be directly involved in collecting, sorting, processing, and utilizing waste in the school environment.